Deoxybenzoin-containing polysulfones and polysulfoxides: Synthesis and thermal properties. (10th February 2016) - Mir, Aabid A.; Wagner, Sebastian; Krämer, Roland H.; Deglmann, Peter; Emrick, Todd
Abstract: Novel poly(arylene ether) sulfones, sulfoxides, and sulfides containing deoxybenzoin subunits were synthesized by step growth polymerization involving bishydroxydeoxybenzoin (BHDB) and the corresponding sulfur-containing monomers. The isolated polymers demonstrated good solubility in organic solvents, making them easily processible into transparent, flexible, and creasable films upon solution casting. All of the polymers prepared exhibited exceptionally low flammability characteristics, with total heat release (THR) values as low as 6 J/g-K, and char yield values as high as 54%. Inclusion of deoxybenzoin monomers into polysulfones with 4, 4'-biphenyl led to heat release capacity (HRC) values less than half that of commercial polysulfones in use today, placing deoxybenzoin-based polysulfones and polysulfoxides into the ultra-low flammability category.